Design, electrosynthesis and electrochromic properties of conjugated microporous polymer films based on butterfly-shaped diphenylamine-thiophene derivatives. (20th December 2022) - Hu, Bin; Li, Jing; Wang, Yihan; Hu, Xianqiu; Shi, Yupeng; Jin, Lin
Highlights: Obtained two novel butterfly-shaped structure monomers. Conjugated microporous polymers films can be obtained via electropolymerization. Both the PTTPBA and PTTPTA films showed good electrochemical properties. PTTPBA and PTTPTA films exhibited faster response time. Abstract: Conjugated microporous polymers (CMPs) have attracted much attention owing to the existence of extended π-conjugated skeleton, which possess 3D cross-linked framework that benefits for charge transporting in the polymer film due to the non-planar structure for active groups of the monomers. In this manuscript, two novel CMP films based on butterfly-shaped diphenylamine-thiophene derivatives were synthesized via electropolymerization. Both the polymer film showed good electrochemical properties. The microstructure and thickness of polymer films were characterized by SEM, TEM and AFM, and the results indicated uneven surface of the polymer films were observed, which consisted of many particles and aggregations. The change of bridge group has little effect on the showing color feature, both the films displayed reversible color change from green to blue upon the different applied potentials. Comparing with the linear intermediate polymer films, both the CMP films held faster switching time (about 1 s). Moreover, the polymers possessed good coloration efficiency and stability, which promised them potential application for electrochromic device. Graphical abstract: Image, graphical abstract